The IGF-1R/AKT pathway has opposing effects on Nutlin-3a-induced apoptosis. Issue 11 (2nd November 2017) - Davaadelger, Batzaya; Perez, Ricardo E.; Zhou, Yalu; Duan, Lei; Gitelis, Steven; Maki, Carl G.
ABSTRACT: Nutlin-3a is a small molecule MDM2 antagonist and potent activator of wild-type p53. Nutlin-3a disrupts MDM2 binding to p53, thus increasing p53 levels and allowing p53 to inhibit proliferation or induce cell death. Factors that control sensitivity to Nutlin-3a-induced apoptosis are incompletely understood. In this study we isolated cisplatin-resistant clones from MHM cells, an MDM2-amplified and p53 wild-type osteosarcoma cell line. Cisplatin resistance in these clones resulted in part from heightened activation of the IGF-1R/AKT pathway. Interestingly, these cisplatin resistant clones showed hyper-sensitivity to Nutlin-3a induced apoptosis. Increased Nutlin-3a sensitivity was associated with reduced authophagy flux and a greater increase in p53 levels in response to Nutlin-3a treatment. IGF-1R and AKT inhibitors further increased apoptosis by Nutlin-3a in parental MHM cells and the cisplatin-resistant clones, confirming IGF-1R/AKT signaling promotes apoptosis resistance. However, IGF-1R and AKT inhibitors also reduced p53 accumulation in Nutlin-3a treated cells and increased autophagy flux, which we showed can promote apoptosis resistance. We conclude the IGF-1R/AKT pathway has opposing effects on Nutlin-3a-induced apoptosis. First, it can inhibit apoptosis, consistent with its well-established role as a survival-signaling pathway. Second, it can enhance Nutlin-3a induced apoptosis through a combination of maintaining p53 levels and inhibiting pro-survival autophagy.